Comparison of physicochemical properties of suppositories containing starch hydrolysates - Piotr Belniak; Katarzyna Świąder; Michał Szumiło; Aleksandra Hyla; Ewa Poleszak (Elsevier, 2017)
The purpose of this work was to determine the effect of starch hydrolysates (SH) on the physicochemical properties of suppositories. The study was conducted with suppositories with acetaminophen (AAP) a typical antipyretic analgesic, as model drug on lipophilic (cocoa butter) and hydrophilic base (polyethylene glycol 1500 + 400). The suppositories with and without the addition of SH were examined for physicochemical tests according to European Pharmacopoeia 8th edition (Ph. Eur.): the uniformity of mass of single-dose preparation test, the softening time determination of lipophilic suppositories test, the disintegration of suppositories test, and dissolution test with flow-through apparatus. The results confirm the possibility of using starch hydrolysates as a cheap and safe addition to modify physicochemical properties of suppositories.